4D printing of shape memory polyurethane via stereolithography. (April 2018) - Zhao, Tingting; Yu, Ran; Li, Xinpan; Cheng, Bing; Zhang, Ying; Yang, Xin; Zhao, Xiaojuan; Zhao, Yulei; Huang, Wei
Graphical abstract: Highlights: A type of photopolymer composed polyurethane acrylate is synthesized. The photopolymer is applied in SLA technique to print shape memory polymers. The printed samples show excellent shape memory performance. The printed samples have high mechanical strength and good toughness. Abstract: In our research, a type of polyurethane acrylate is successfully synthesized and then compounded with epoxy acrylate and isobornyl acrylate as well as radical photoinitiator to get photopolymer. Afterwards, the photopolymer is applied through stereolithography 3D printing to fabricate shape memory polymers. The photopolymer is proved to have high UV-curing activity and the printing accuracy is high. Fold-deploy test and shape memory cycles measurements prove the excellent shape memory performance of the printed objects, including high shape recovery rate, shape fixity and recovery and excellent endurance. The shape fixity and recovery ratios are 96.77 ± 0.06% and 100.00 ± 0.08%, respectively. Tensile test at 70 °C shows that the recovery stress of printed objects can reach as high as 6.4 MPa. Mechanical test shows the printed objects have high strength and good toughness. With excellent shape memory performance, good mechanical properties and high printing accuracy, such material has great potential applications in many fields.